Effect of screentime in college students during the COVID-19 online classes on their neck posture and postural control: an observational study - P., Chaitra Bhat; Saji, Rajina; K. B., Riyas Basheer (International Journal of Research in Medical Sciences, 2024)
Background: Corona virus which is the source of severe acute pulmonary syndrome causes an airway tract contamination (COVID 19). Prolonged sitting for online classes in the college students leads to the enlarged postural deviation, increased low back pain. Prolonged static contraction of skeletal muscles of the cervical region, lower back leads to impaired flow of blood to the muscle groups together with edema and accumulation of waste metabolites will trigger the muscle spasm. Methods: Total 30 college students aged between 18-25 years who attended the online classes during COVID-19 were included in this study by using a questionnaire. The outcome measures used were the measurement of CV angle, SEBT and BBS. The postural control was estimated by using star excursion balance test and Berg balance scale. Results: Using Karl Pearson’s correlation coefficient, a positive correlation was observed between CV angle and BBS (r = 0.82). Between BMI and CV angle there exists a statistically significant negative correlation (r = -0.564). Conclusions: This study proved that there exists a forward neck posture in the students who attended the online classes during the COVID-19 pandemic and that also affected their postural control.